2007
DOI: 10.1002/ajmg.a.31872
|View full text |Cite
|
Sign up to set email alerts
|

Familial thoracic aortic dilation and bicommissural aortic valve: A prospective analysis of natural history and inheritance

Abstract: The autosomal dominant inheritance of bicommissural aortic valve (BAV) (Online Mendelian Inheritance in Man #109730) in some families is well-documented; however, the inheritance of BAV with thoracic aortic aneurysm (TAA) is less clear. Whether the aneurysm is secondary to hemodynamic perturbation related to the valve abnormality or a primary manifestation of the disorder remains controversial. Guidelines are needed regarding the follow-up and treatment of these patients and their families. Thirteen families w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(152 citation statements)
references
References 45 publications
(42 reference statements)
5
138
0
9
Order By: Relevance
“…Our results also suggest that genetic testing and cardiac imaging with at least TTE should be offered to all FDRs and SDRs of patients with suspected NS‐TADs. Mutation carriers should undergo further imaging (MRI or CT scan), focusing on thoracic aorta and/or other arterial trees based on the causative gene mutation 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74. For example, ACTA2‐mutation carriers should be monitored for coronary artery disease and occlusive cerebrovascular disease, in addition to the currently recommended routine imaging tests 32.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggest that genetic testing and cardiac imaging with at least TTE should be offered to all FDRs and SDRs of patients with suspected NS‐TADs. Mutation carriers should undergo further imaging (MRI or CT scan), focusing on thoracic aorta and/or other arterial trees based on the causative gene mutation 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74. For example, ACTA2‐mutation carriers should be monitored for coronary artery disease and occlusive cerebrovascular disease, in addition to the currently recommended routine imaging tests 32.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty four of the relatives (22%) were diagnosed with TAA in the presence of a normal tricuspid aortic valve. 32 In addition, Keane et al reported that aortic size in BAV patients was larger than in control patients. They observed comparable degrees of aortic regurgitation, stenosis or mixed lesions, and concluded that intrinsic pathology appears to be responsible for aortic enlargement.…”
Section: Bicuspid Aortic Valve: Clinical and Genetic Aspectsmentioning
confidence: 99%
“…This root phenotype has been proposed to be the form of bicuspid aortopathy most likely to be associated with a genetic cause. 3,13,20,24,[31][32][33] Although rare, the most feared complication in BAV patients is thoracic aortic dissection, which has been reported at young age. 34 Whereas the lifetime risk of aortic dissection in BAV patients was initially reported around 5%, recent studies show a lifetime risk of aortic dissection of less than 1% in BAV patients and a normal life expectancy.…”
Section: Bicuspid Aortic Valve: Clinical and Genetic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 -19 While the familial association of BAV with aortopathy has been well described, few studies have addressed aortopathy in BAV relatives with normal, trileaflet aortic valves. 8,10,20,21 Biner et al demonstrated that the aortic root is functionally abnormal and dilated in up to 32% of FDRs. 21 However, other studies found a lower prevalence of aortic dilatation among BAV relatives.…”
Section: Introductionmentioning
confidence: 99%